COMPARATIVE ASSESSMENT OF QUALITY OF LIFE IN PATIENTS WITH SCLEROSIS OF THE DEEP LIMB AFTER HIGH AMPUTATION OF THE LOWER LIMB (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Today, diabetes mellitus is the most common endocrine disease in the world. According to the IDF Diabetes Atlas 2025, there are 589 million people with diabetes mellitus worldwide, and it is projected that 853 million people will suffer from diabetes by 2050.